2010
DOI: 10.1002/cbdv.201000158
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Branched Dialkylpyrazines in Myxobacteria

Abstract: The biosynthesis of the volatiles 2,5- and 2,6-diisopropylpyrazine (2 and 3, resp.) released by the myxobacteria Nannocystis exedens subsp. cinnabarina (Na c29) and Chondromyces crocatus (strains Cm c2 and Cm c5) was studied. Isotopically labeled precursors and proposed pathway intermediates were fed to agar plate cultures of the myxobacteria. Subsequently, the volatiles were collected by use of a closed loop stripping apparatus (CLSA), and incorporation into the pyrazines was followed by GC/MS analysis. [(2)H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Their potential receptors are not known because only few bacterial communication mechanisms have been established so far (see Introduction). Finally, in some cases they may also serve as a means of detoxification, as recently proposed for some pyrazines[34]. Interestingly, the pyrazines show almost no antimicrobial activity.…”
Section: Resultsmentioning
confidence: 90%
“…Their potential receptors are not known because only few bacterial communication mechanisms have been established so far (see Introduction). Finally, in some cases they may also serve as a means of detoxification, as recently proposed for some pyrazines[34]. Interestingly, the pyrazines show almost no antimicrobial activity.…”
Section: Resultsmentioning
confidence: 90%
“…Another pathway was proposed and validated with the isotope labeling approach [54]. Cheng et al [55] confirmed these results and proposed a novel and widely-accepted biosynthetic pathway for IPMP (Figure 4(Ab) and Figure 5) that is consistent with the results of Nawrath [56] (Figure 4 Studies on the formation of the pyrazine ring in plants are scarcely found. On an AcadĂ©mie Amorim in 2003, Roujou de BoubĂ©e [57] issued the studies on IBMP in grapes and wines.…”
Section: Precursors To and Formation Of The Pyrazine Ringmentioning
confidence: 60%
“…The proposed biosynthesis pathways of pyrazines (A) and the hypothesized pathway and precursors for 3-alkyl-2-methoxypyrazines in grapes and wine (B). (A-a) is from Murray et al[46], (A-b) from Cheng et al[55], and (A-c) from Nawrath et al[56]. The colors of red and blue display the origination of hemical groups.…”
mentioning
confidence: 99%
“…In brief, sterols were isolated from frozen, ground mycelia using a 3:1 (v/v) mixture of chloroform and methanol, subsequent saponification with 10% (w/v) potassium hydroxide in methanol, followed by extraction in n-hexane. Sterol extracts were derivatized with 2,2,2trifluoro-N-methyl-N-(trimethylsilyl) acetamide (MSTFA) and analyzed by gas chromatography/mass spectrometry (GC/MS) as described in (Nawrath et al 2010). The sterol biosynthesis intermediates were identified by comparing their mass spectra with data available from databases and the literature.…”
mentioning
confidence: 99%